Exosomal non-coding RNAs: key regulators of inflammation-related cardiovascular disorders - Mohamed J. Saadh; Faris Anad Muhammad; Rafid Jihad Albadr; Gaurav Sanghvi; Suhas Ballal; Piyus Kumar Pathak; Lakshay Bareja; Zafar Aminov; Waam Mohammed Taher; Mariem Alwan; Mahmood Jasem Jawad; Ali M. Ali Al-Nuaimi (European Journal of Medical Research)
Abstract Inflammation is a complex, tightly regulated process involving biochemical and cellular reactions to harmful stimuli. Often termed “the internal fire”, it is crucial for protecting the body and facilitating tissue healing. While inflammation is essential for survival, chronic inflammation can be detrimental, leading to tissue damage and reduced survival. The innate immune system triggers inflammation, closely linked to the development of heart diseases, with significant consequences for individuals. Inflammation in arterial walls or the body substantially contributes to atherosclerotic disease progression, affecting the cardiovascular system. Altered lipoproteins increase the risk of excessive blood clotting, a hallmark of atherosclerotic cardiovascular disease and its complications. Integrating inflammatory biomarkers with established risk assessment techniques can enhance our ability to identify at-risk individuals, assess their risk severity, and recommend appropriate CVD prevention strategies. Exosomes, a type of extracellular vesicle, are released by various cells and mediate cell communication locally and systemically. In the past decade, exosomes have been increasingly studied for their vital roles in health maintenance and disease processes. They can transport substances like non-coding RNAs, lipids, and proteins between cells, influencing immune responses and inflammation to elicit harmful or healing effects. This study focuses on the critical role of inflammation in heart disease progression and how non-coding RNAs in exosomes modulate the inflammatory process, either exacerbating or alleviating inflammation-related damage in the cardiovascular system.